GIZ’s evaluation system - Unit, GIZ Evaluation (GIZ GmbH, 2018)
This provides a general description of GIZ’s new evaluation system, wh ich is designed to implement our new policy and to achieve the objecti ves of evaluation reform. This general description is accompanied by t wo other documents that provide supplementary details of GIZ’s key eva luation instruments: project evaluations for BMZ business and corporat e strategic evaluations. They are geared in particular to GIZ staff me mbers who commission, implement or support evaluations and to evaluato rs who conduct evaluations on behalf of GIZ as well as repre-sentative s of commissioning parties, clients and cooperation partners. The curr ent versions are very much a ‘work in progress’ in many regards. We ar e well aware that we will only be able to meet our own high expectatio ns of our evaluations if we continue to develop their quality in dialo gue with project staff, our commissioning parties, clients and partner s and with evaluation practitioners and experts from the academic, sci entific and research community. We look forward to taking on this task and to sharing our experience with all interested parties.